Labour market integration of Ukrainian forced migrants in Europe: spatial patterns, structural barriers and human capital implications - Husieva, Nataliia; Bodnariuk, Olexander (Human Geography Journal, 2026)
This article presents a human-geographical analysis of the labour market integration patterns of Ukrainian forced migrants in European host countries in the context of russia's full-scale armed aggression against Ukraine. The theoretical framework draws on human capital theory (G. Becker, T. Schultz), the segmented labour market theory (P. Doeringer, M. Piore), nd the institutional country-comparative perspective on labour market integration (R. Ortlieb, L. Knappert). The empirical base comprises large-scale survey data from UNHCR (over 6,000 observations, mid-2025), supplemented by Eurostat and OECD statistics. Linear probability models with robust standard errors are employed to identify the determinants of employment and qualification matching.The overall employment rate of Ukrainian forced migrants aged 20–64 in Europe stands at 57%, which is 22 percentage points (p.p.) below the comparable rate for host-country nationals. A pronounced geographical differentiation is identified: the highest employment rates are recorded in countries neighbouring or geographically proximate to Ukraine – Estonia (72%), Hungary (71%), Poland (68%) – while Switzerland (29%), Norway (37%) and Denmark (39%) form the lowest-performing group. These differences persist regardless of migrants' individual characteristics, indicating that host country labour market structure, institutional environment, and integration policy play a determining role.Special attention is devoted to the phenomenon of skills underutilisation (skill mismatch): nearly 60% of employed forced migrants work below their qualification level, and the median wage gap compared to local workers reaches 40%. Unlike general employment rates, which gradually improve with duration of stay, skills mismatch does not diminish over time, pointing to structural rather than merely adaptive barriers. The key determinants of qualification mismatch are identified as: sectoral discontinuity after displacement (−29 p.p.), as well as complex credential recognition procedures, absence of suitable vacancies, and labour market discrimination – each reducing the probability of qualified employment by 11–19 p.p. Estimates suggest that removing these barriers could generate annual GDP gains of up to 0.7 % for host countries. It is argued that preserving and developing the competencies of forced migrants, even within the framework of employment abroad, represents a critical human capital resource for Ukraine's post-war reconstruction. Practical policy recommendations are formulated covering language training, qualification recognition reform, and institutional support for quality employment.